Effects of difference C/N ratio on water quality of white leg shrimp (Litopenaeus vannamei) cultivation - Samadan, Gamal M; Muchdar, Fatma; Ridwan, Ismawati (Depik, 2023)
Biotechnology is used to apply technology to the C/N ratio by stimulating the activities of heterotrophic microorganisms, which derive food from carbon and nitrogen substrates in a certain ratio. The goal of this research was to see how the optimal carbon-nitrogen ratio affected water quality and floc volume in white leg shrimp (Litopenaeus vannamei) farming. This study took place in the UPT Integrated Laboratory Unkhair in Ternate City in July and August 2021. A fully randomized design (CRD) with four treatments and three replications was used in this investigation. Different C/N ratios had an effect on ammonia, nitrite, nitrate, floc volume, and feed conversion ratio, according to the research. The water quality parameters are still suitable for white leg shrimp cultivation. In white leg shrimp culture, the addition of C-organic molasses (different C/N ratios) was able to reduce the concentrations of (NH3), (NO2), and (NO3), and also greatly increase the flock volume and streamline the feed conversion ratio.Keywords:C/N RatioVannameiWastewaterBiofloc